Energy Stopping Power of Electrons in the Energy Range (0.01- 1000 MeV) In Some Human Body Tissues and Water - Saeed S. Kamoon; Shaker M. Murbat; Fatima H. Fakhri (Journal of Madenat Alelem University College, 2017)
Electron accelerator is considered as an important tool in cancer radio-therapy and it providing unique choice in treatment of superficial tumor. In this paper, the mass stopping power of electrons has been calculated in biomedical human substances such as bones, soft-tissues and water with energy range of (10 keV-1000 MeV)using two methods. The first methodis done by calculating the energy loss of electrons in the tissue as one compound. The second method is by calculating the collision energy loss of electrons for each element of the compositions of bone, soft-tissue and water, and then calculates the collision energy loss of the tissue, where the tissue was considered to be made up of thin layers of pure elements (H, C, N, O, Na, Mg, P, S, Cl, K, Ca, Fe and Zn). The present results of the mass stopping power (dE/dX) for bone, tissue(soft) and waterwere compared for the two methods with the standard published results (ESTAR PROGRAM). The results are found in excellent agreement with the standard published data, where the error doesn’t exceeds 0.3% when the first method was used. But it was found that the error is high when the second method is used. Therefore, werecommended using the first method and treating the tissue as one compound instead of it is composed of thin layers of pure elements.